Central Asia after two decades of independence - Richard Pomfret (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
After becoming independent in 1991, the five Central Asian countries pursued differing transition paths from the defunct central planning. This paper analyses the connection between economic policies and performance during the 1990s and 2000s. Performance over the two decades has been determined by resource endowments rather than by policy. International relations, which were predicted to centre on a new Great Game among external powers, have been more muted than anticipated, centring on geopolitics and pipelines, and with a consequence of hampering desirable economic cooperation within Central Asia. Prospects for significant change in the near future are limited because by the end of the 1990s the window of opportunity for policy initiatives had shut and entrenched political regimes had little incentive to sponsor major reforms.
Keywords: P20; O53; 330; Central Asia; transition from central planning